Perancangan Sistem Database Kinerja Penelitian Menggunakan Excel Macro di LP2M Politeknik Jambi - Muhammad hadi Saputra; Sigit Kurniawan; Febri Distriyan (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
The Research and Community Service Institute (LP2M) of Politeknik Jambi is responsible for managing the research performance of lecturers and students. The manual data management process often leads to delays in report preparation, reduced data accuracy, and difficulties in analysis. This study designs a research performance management system using Excel Macro as a simple and lightweight solution that does not require complex database software. The method consists of requirement analysis, data structure design, development of automated input forms, and macro modules for validation, recapitulation, and report generation. The implementation results show that the system can automatically generate performance reports, accelerate the recapitulation process by up to 60%, and reduce data entry errors. The novelty of this research lies in the use of Excel Macro as an alternative tool for managing research performance in higher education institutions, where such systems are typically built using web-based applications or dedicated database platforms. This system proves to be more efficient and user-friendly, thereby improving the effectiveness of research performance management at LP2M Politeknik Jambi.